2021
DOI: 10.1002/hbm.25652
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging measures of iron and gliosis explain memory performance in aging

Abstract: Evidence from animal and histological studies has indicated that accumulation of iron in the brain results in reactive gliosis that contributes to cognitive deficits. The current study extends these findings to human cognitive aging and suggests that magnetic resonance imaging (MRI) techniques like quantitative relaxometry can be used to study iron and its effects in vivo. The effects of iron on microstructure and memory performance were examined using a combination of quantitative relaxometry and multicompart… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 65 publications
(117 reference statements)
4
11
1
Order By: Relevance
“…The indirect effects revealed that the age-related decline in episodic memory was significantly mediated by hippocampal diffusion, but not hippocampal volume. These finding are consistent with previous unimodal multi-compartment diffusion-weighted (Radhakrishnan et al, 2020;Venkatesh et al, 2021) and T1-weighted (Raz et al, 1998;Rodrigue & Raz, 2004;Tisserand et al, 2000) studies that included younger and older adults. However, an advantage of the current multimodal approach is that these unique effects for each structural MRI modality were assessed within the same sample, revealing that diffusion was more sensitive to memory deficits in aging than volume.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The indirect effects revealed that the age-related decline in episodic memory was significantly mediated by hippocampal diffusion, but not hippocampal volume. These finding are consistent with previous unimodal multi-compartment diffusion-weighted (Radhakrishnan et al, 2020;Venkatesh et al, 2021) and T1-weighted (Raz et al, 1998;Rodrigue & Raz, 2004;Tisserand et al, 2000) studies that included younger and older adults. However, an advantage of the current multimodal approach is that these unique effects for each structural MRI modality were assessed within the same sample, revealing that diffusion was more sensitive to memory deficits in aging than volume.…”
Section: Discussionsupporting
confidence: 92%
“…Neurite Orientation Dispersion and Density Imaging (NODDI) is a multi-compartment modelling approach that yields separate estimates of diffusion within (intracellular) and between (dispersion) cells and from non-cellular sources (free) (Zhang et al, 2012); which may be more sensitive that single tensor metrics to diffusion in gray matter (Venkatesh et al, 2020). NODDI studies have shown age-related increases in all diffusion metrics in the hippocampus (Franco et al, 2021;Metzler-Baddeley et al, 2019;Nazeri et al, 2015;Radhakrishnan et al, 2020;Venkatesh et al, 2020Venkatesh et al, , 2021 and that higher hippocampal diffusion relates to worse delayed free recall in younger and older adults (Radhakrishnan et al, 2020;Venkatesh et al, 2021). Thus, whereas both hippocampal macrostructure and microstructure decline with age, hippocampal microstructure may uniquely contribute to age-related declines in episodic memory performance, although this is based on very few NODDI studies that examined diffusion-memory relationships with select memory measures.…”
Section: Introductionmentioning
confidence: 99%
“…Striatal Fe was found to be highest in the elderly who also show increased neuroinflammation when assessed through myo-inositol, a marker of activated microglia in the brain, measured by magnetic resonance spectroscopy [50]. Another recent study found decreases in memory performance related to increased Fe, measured by MRI R2* relaxometry, and subsequent gliosis in hippocampus and caudate [51]. Interestingly, a genome-wide association study identified several loci in If a modest systemic inflammation, which invariably involves neuroinflammation, escalates during aging, neuronal Fe export is halted by systemic hepcidin upregulation while neuronal Fe import may continue, leading to accumulation of Fe intracellularly.…”
Section: Brain Iron Neuroinflammation and Cognitive Decline In Agingmentioning
confidence: 98%
“…Striatal Fe was found to be highest in the elderly who also show increased neuroinflammation when assessed through myoinositol, a marker of activated microglia in the brain, measured by magnetic resonance spectroscopy [50]. Another recent study found decreases in memory performance related to increased Fe, measured by MRI R2* relaxometry, and subsequent gliosis in hippocampus and caudate [51]. Interestingly, a genome-wide association study identified several loci in the heme iron metabolism pathway associated with health-span and longevity; multivariate Mendelian randomization of iron-related traits showed a protective effect of transferrin and deleterious effect of serum Fe [52].…”
Section: Brain Iron Neuroinflammation and Cognitive Decline In Agingmentioning
confidence: 99%
“…Susceptibility-weighted imaging is another MRI modality of interest given its sensitivity to iron, which is known to accumulation with age and is thought to contribute to neurodegeneration via inflammation (Venkatesh et al, 2021;Zecca et al, 2004). Age-related increases in iron have been observed in oldest-old adults within the putamen (van Bergen et al, 2018), a subcortical structure known to gradually accumulate iron across the younger adult lifespan (Hallgren and Sourander, 1958).…”
Section: Other Mri Modalitiesmentioning
confidence: 99%